Ageism and Age Discrimination in Old Age: An Overview (Philosophy and Progress, 2016)
Bangladesh is the eighth largest countries in the world with a population of more than 160 million. Today, the number of older persons is about 12 million which represents 7.5 percent of the total population. As increasing the number of older persons gradually their deprivation is also increasing. Age discrimination is a global social issue which affects the health and human rights of millions of older persons around the world, and an issue which deserves the attention of the national and international community. In our country, ageism is observed severely due to low economic capacity, poverty, loss of work and authority, physical inability, changes of social norms and values, breaking the joint family unit, negligence attitudes towards the elderly, individualism and other psycho-social, economic and cultural reasons. Age discrimination affects older men and women across all socio-economic groups, cultures, races and ethnicities.Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014